Nuevo método para la obtención de quitina - Díaz Sánchez, Luisa M. (Universidad de Costa Rica, 2009)
A simple method for the isolation of chitin is described. It is based on the solubility of the biopolymer in concentrated aqueous HCl at low temperature. The solubility diagram of the system chitin-HCl-H2O is discussed as well as the kinetics of the acid-catalyzed hydrolysis of the biomaterial. The hydrolytic degradation of the polymer is estimated to be less than 0,3 %, during the procedure.